Assessing the effects of soil liming with dolomitic limestone and sugar foam on soil acidity, leaf nutrient contents, grape yield and must quality in a Mediterranean vineyard - Olego, Miguel A.; Visconti, Fernando; Quiroga, Miguel J.; de Paz, José M.; Garzón-Jimeno, Enrique (Spanish Journal of Agricultural Research, 2016)
Aluminium toxicity has been recognized as one of the most common causes of reduced grape yields in vineyard acid soils. The main aim of this study was to evaluate the effect of two liming materials, i.e. dolomitic lime and sugar foam, on a vineyard cultivated in an acid soil. The effects were studied in two soil layers (0-30 and 30-60 cm), as well as on leaf nutrient contents, must quality properties and grape yield, in an agricultural soil dedicated to Vitis vinifera L. cv. ‘Mencía’ cultivation. Data management and analysis were performed using analysis of variance (ANOVA). As liming material, sugar foam was more efficient than dolomitic limestone because sugar foam promoted the highest decrease in soil acidity properties at the same calcium carbonate equivalent dose. However, potassium contents in vines organs, including leaves and berries, seemed to decrease as a consequence of liming, with a concomitant increase in must total acidity. Soil available phosphorus also decreased as a consequence of liming, especially with sugar foam, though no effects were observed in plants. For these reasons fertilization of this soil with K and P is recommended along with liming. Grape yields in limed soils increased, although non-significantly, by 30%. This research has therefore provided an important opportunity to advance in our understanding of the effects of liming on grape quality and production in acid soils.